2010
DOI: 10.1007/s00408-010-9277-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality, Depression, and Quality of Life in Patients with Pulmonary Hypertension

Abstract: Pulmonary hypertension is a disabling disease characterized by progressive functional worsening, right heart failure, and death. Although pulmonary hypertension has been associated with poor quality of life, sleep quality has not been investigated in pulmonary hypertension patients. This was a cross-sectional study in which patients (N = 40) were asked to complete standardized questionnaires to assess sleep quality [using Pittsburgh Sleep Quality Index (PSQI)], insomnia, sleepiness, dyspnea, depression, restle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 29 publications
6
43
1
Order By: Relevance
“…27 We measured dyspnea severity during activity using the MMRC scale because the MMRC score has been previously used to quantify functional impairment due to dyspnea in patients with PAH. 33 Patients in our study reported an improvement in dyspnea perception using the MMRC in the IMT group compared with the control group after training. However, the minimal clinically important threshold has not been established, but a difference of 1 grade on the MMRC scale is considered to be indicative of a change in perceived dyspnea that is clinically significant in COPD.…”
Section: T a B L E 4 • Effects Of Imt On Dyspnea And Fatigue Perceptimentioning
confidence: 89%
“…27 We measured dyspnea severity during activity using the MMRC scale because the MMRC score has been previously used to quantify functional impairment due to dyspnea in patients with PAH. 33 Patients in our study reported an improvement in dyspnea perception using the MMRC in the IMT group compared with the control group after training. However, the minimal clinically important threshold has not been established, but a difference of 1 grade on the MMRC scale is considered to be indicative of a change in perceived dyspnea that is clinically significant in COPD.…”
Section: T a B L E 4 • Effects Of Imt On Dyspnea And Fatigue Perceptimentioning
confidence: 89%
“…Several studies have shown that depression and anxiety are frequently reported symptoms in PH [9,10,11,12,14], and thus screening for mental disorders has been recommended [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients often appear healthy at rest and thus might not be taken seriously by health care providers or their environment in their constrained daily life [8]. Anxiety and depression are highly prevalent in chronic diseases and have also been commonly found in prevalent PAH patients under chronic therapy [9,10,11,12,13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis of pulmonary arterial hypertension (PAH) carries deep psychological 1 and financial 2 consequences.…”
Section: Introductionmentioning
confidence: 99%